2022
DOI: 10.1101/2022.07.29.502066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-biased infections scale to population impacts for an emerging wildlife disease

Abstract: Demographic factors are fundamental in shaping infectious disease dynamics. Aspects of populations that create structure, like age and sex, can affect patterns of transmission, infection intensity and population outcomes. However, studies rarely link these processes from individual to population-scale effects. Moreover, the mechanisms underlying demographic differences in disease are frequently unclear. Here, we explore sex-biased infections for a multi-host fungal disease of bats, white-nose syndrome, and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 100 publications
0
5
1
Order By: Relevance
“…While we did not routinely collect age data due to the difficulties of ageing little brown bats more than six months after birth, other studies have indicated no changes in the number of juveniles in the summer maternity season [ 42 ]. Sex-biases in infection have reduced the number of female bats as WNS established [ 43 ]; however, females are generally slighter heavier than males which should result in a pattern opposite of our findings. Third, bats in some populations have evolved higher pathogen resistance [ 33 , 35 ] which may have reduced selection for increased body mass, particularly if fatter bats face other trade-offs, such as reduced flight abilities [ 44 , 45 ].…”
Section: Discussioncontrasting
confidence: 84%
“…While we did not routinely collect age data due to the difficulties of ageing little brown bats more than six months after birth, other studies have indicated no changes in the number of juveniles in the summer maternity season [ 42 ]. Sex-biases in infection have reduced the number of female bats as WNS established [ 43 ]; however, females are generally slighter heavier than males which should result in a pattern opposite of our findings. Third, bats in some populations have evolved higher pathogen resistance [ 33 , 35 ] which may have reduced selection for increased body mass, particularly if fatter bats face other trade-offs, such as reduced flight abilities [ 44 , 45 ].…”
Section: Discussioncontrasting
confidence: 84%
“…White‐nose syndrome (WNS) is an emerging infectious disease caused by the fungal pathogen Pseudogymnoascus destructans (Lorch et al, 2011; Warnecke et al, 2012), which has had devastating effects on bat populations (Frick et al, 2015; Langwig et al, 2012, 2016). WNS exhibits seasonal infection dynamics that are driven by the environmental reservoir and host–pathogen ecology (Hoyt et al, 2021; Kailing et al, 2023; Langwig et al, 2021; Langwig, Frick, et al, 2015). Pseudogymnoascus destructans can persist for long periods of time in the environment, which results in widespread infection when hosts return to hibernacula (subterranean sites where bats hibernate in the winter) in the fall (Campbell et al, 2019; Hicks et al, 2021; Hoyt et al, 2015, 2020; Langwig, Frick, et al, 2015; Lorch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Males and females differ in their genetics, physiology and behaviour—all of which can alter the likelihood and severity of infection [16] and the spread of pathogens [712]. Many attempts to define whether males or females are more likely to be damaged by a pathogen and become the ‘sicker sex’ have centred on host susceptibility (i.e.…”
Section: Introductionmentioning
confidence: 99%